2014
DOI: 10.1016/j.baga.2013.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal bursting as a pathophysiological mechanism in Parkinson's disease

Abstract: Despite remarkable advances in Parkinson's disease (PD) research, the pathophysiological mechanisms causing motor dysfunction remain unclear, possibly delaying the advent of new and improved therapies. Several such mechanisms have been proposed including changes in neuronal firing rates, the emergence of pathological oscillatory activity, increased neural synchronization, and abnormal bursting. This review focuses specifically on the role of abnormal bursting of basal ganglia neurons in PD, where a burst is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 129 publications
1
38
1
Order By: Relevance
“…It is worth noting that a variety of burst metrics exist and, unfortunately, there is no consensus on what counts and what does not count as a burst, particularly when neural activity is strongly modulated by an oscillatory input (Lobb, 2014). This can be seen in our anesthetized recordings which clearly showed a significant change in the firing pattern but generated conflicting results between burst detection methods: the commonly used PS method finding a significantly increased rate of weaker intensity bursting and the RGS method finding a significantly decreased rate of bursting of a similar intensity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that a variety of burst metrics exist and, unfortunately, there is no consensus on what counts and what does not count as a burst, particularly when neural activity is strongly modulated by an oscillatory input (Lobb, 2014). This can be seen in our anesthetized recordings which clearly showed a significant change in the firing pattern but generated conflicting results between burst detection methods: the commonly used PS method finding a significantly increased rate of weaker intensity bursting and the RGS method finding a significantly decreased rate of bursting of a similar intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Using a variety of burst methodologies (Lobb, 2014), previous studies in MPTP-treated monkeys have shown that bursting is enhanced in the traditional basal ganglia output nuclei of the globus pallidus internal segment and the SNpr (Bergman et al, 1994; Boraud et al, 1998; Wichmann et al, 1999; Wichmann and Soares, 2006) suggesting that abnormally increased bursting could drive motor dysfunction in Parkinson’s disease. In our study, SNpr neuron activity in awake, head-restrained mice was significantly more regular than in the anesthetized 6-OHDA condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DBS in PD is one of the most common treatment options when patients develop disabling motor symptoms, with the subthalamic nucleus (STN) and globus pallidus interna (GPi) being the primary stimulation targets (Miocinovic et al, 2013). However, following its incidental discovery in 1987 (Benabid et al, 1987), the mechanism of action of the DBS therapy is still debated (Da Cunha et al, 2015;DeLong and Wichmann, 2012;Dostrovsky and Lozano, 2002;Lobb, 2014;McIntyre and Hahn, 2010) and its effects are not consistent for all patients. Proposals range from DBS introducing antidromic action potentials stimulating the motor cortex (Li et al, 2012) to DBS changing the large-scale structural connectivity of the brain (van Hartevelt et al, 2014).…”
Section: Parkinson's Diseasementioning
confidence: 96%
“…This can be explained by the synchronized activity of the population during the burst, which stabilizes neural information transmission against different types of noise 3 . On the other hand, increased bursting activity has been found in various neurological diseases such as epilepsy or Parkinson's disease and may thus also act disruptively on neural communication, if exceeding certain levels of occurrence 4,5 . Thus, mean-field models of collective bursting are important for theoretical investigations of information transmission between neural populations as well as transitions between healthy and pathological states of population dynamics.…”
Section: Introductionmentioning
confidence: 99%